Dynamic multiscale metabolic network modeling of Chinese hamster ovary cell metabolism integrating N‐linked glycosylation in industrial biopharmaceutical manufacturing. Issue 1 (11th October 2020) - Erklavec Zajec, Vivian; Novak, Uroš; Kastelic, Miha; Japelj, Boštjan; Lah, Ljerka; Pohar, Andrej; Likozar, Blaž
Abstract: Experimental and modeling work, described in this article, is focused on the metabolic pathway of Chinese hamster ovary (CHO) cells, which are the preferred expression system for monoclonal antibody protein production. CHO cells are one of the primary hosts for monoclonal antibodies production, which have extensive applications in multiple fields like biochemistry, biology and medicine. Here, an approach to explain cellular metabolism with in silico modeling of a microkinetic reaction network is presented and validated with unique experimental results. Experimental data of 25 different fed‐batch bioprocesses included the variation of multiple process parameters, such as pH, agitation speed, oxygen and CO2 content, and dissolved oxygen. A total of 151 metabolites were involved in our proposed metabolic network, which consisted of 132 chemical reactions that describe the reaction pathways, and include 25 reactions describing N‐glycosylation and additional reactions for the accumulation of the produced glycoforms. Additional eight reactions are considered for accumulation of the N‐glycosylation products in the extracellular environment and one reaction to correlate cell degradation. The following pathways were considered: glycolysis, pentose phosphate pathway, nucleotide synthesis, tricarboxylic acid cycle, lipid synthesis, protein synthesis, biomass production, anaplerotic reactions, and membrane transport. With the applied modeling procedure, different operational scenarios and fed‐batch techniques can be tested. Abstract : Experimental and modeling work, described in this article, is focused on the metabolic pathway of Chinese hamster ovary cells, which are the preferred expression system for monoclonal antibody protein production. Here, an approach to explain cellular metabolism with in silico modeling of a microkinetic reaction network is presented and validated with unique experimental results.